Actual questions of diagnosis and treatment of idiopathic short stature in children - Samson, O.Ya.; Sprynchuk, N.A.; Bolshova, O.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
Among all patients with short stature, the examination revealed the normal content of growth hormone (basal and stimulated levels) and reduced or normal levels of insulin-like growth factor-I in the majority, which automatically excludes these patients from a cohort of growth hormone deficiency. The vast majority of these patients had a diagnosis of idiopathic short stature; sometimes, there were isolated cases of a syndrome of biologically inactive growth hormone. The article discusses the diagnostic differences between these states and therapeutic interventions, by predicting the effectiveness of treatment.